South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes impact of debt on growth in South Africa. A permanent increase of four percentage points of gross domestic product (GDP) in national government expenditure underlies the doubling of public debt in the last decade. The wage bill accounted for most of the expenditure increase (64 percent), followed by the interest bill (23 percent). The debt expansion, thus, financed a countercyclical fiscal policy centered on current spending, which likely shielded the impact of subdued economic activity, but had limited permanent effects on growth. Had resources devoted to wage increases and debt service payments been invested in more productive outlays, such as highly productive capital expenditure and reforms in key network industries, the growth gains would have been higher. The spending increase that drove the large debt accumulation helped smooth the impact of the global financial crisis, but likely did not have a material impact on growth.